Albrecht et al.: Schriftsteller der DDR - Peter W Krawutschke (GDR Bulletin, 1977)
Günter Albrecht, Kurt Böttcher, Herbert Greiner-Mai, Paul Günter Krohn, eds. Leipzig: VEB Bibliographisches Institut, 1974. (Meyers Taschenlexikon), 656 p., 19,80 DM.